Pemanfaatan Bahan Alami Sebagai Rodentisida Dan Pengusir Tikus Pada Kelompok Tani Di Desa Negeri Agung, Kecamatan Gunung Pelindung, Kabupaten Lampung Timur - Emantis Rosa; Yulianti; Enur Azizah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
One of the pests that is a problem for plants is rats. As a result, it can cause a decrease in production, crop failure and can even cause plants to die and losses to farmers. To overcome rat pest attacks, it is necessary to control them. Farmers have not received much information on control efforts derived from natural ingredients. Hence, in this service activity, outreach was carried out on "The Use of Natural Ingredients as Rodenticides and Rat Repellents to Farmer Groups in Negeri Agung Village, Gunung Pelindung District." The results show an increase in knowledge and understanding among participants from the low category of 40% to the high category of 90%, with an average increase of 50%.